Falhas na manutenção de pneus em uma frota de caminhões: uma análise das causas aplicando a ferramenta FMEA - ANJOS, Jhulyane do Socorro dos (2019)
This work aimed to propose measures to support the management of tire maintenance in the vehicle fleet of a beverage distributor through the application of the Failure Modes Analysis and its Effects (FMEA) tool. To better structure the FMEA, we used quality tools such as: Brainstorming, Ishikawa Diagram, Pareto Diagram and 5W1H action plan. The Brainstorming technique was used to collect data from those responsible for the sector that coordinates tire maintenance. The Ishikawa Diagram tool was used to analyze causes and analysis. For the interpretation of the data and determination of the priority causes, the Pareto Diagram technique was used, where it was possible to visualize the causes that most influenced the tire failures. With the 5W1H, a plan of action was developed for the problems identified as priorities, establishing a checklist to monitor and avoid overloading trucks, pressure control plan, training of the person responsible for the calibration procedure, periodic review of the general brake operation, integration plan for new employees and defensive driving training and economical driving for vehicle drivers. The application of the FMEA tool was efficient for analysis of failures that occur in the maintenance of tires, achieving benefits to better act on the control and elimination of risks, guaranteeing better results for the sector.